2016
DOI: 10.1080/00918369.2016.1247537
|View full text |Cite
|
Sign up to set email alerts
|

Methods Used and Topics Addressed in Quantitative Health Research on Gay, Bisexual and Other Men Who Have Sex With Men: A Systematic Review of the Literature

Abstract: Research on sexual minority men (gay, bisexual, and other men who have sex with men) was examined with regard to the measures of sexual orientation used, the methods of research, and the main health outcomes under study. A systematic review of English-language quantitative studies was conducted focused on the health of sexual minority men published in 2010 (n = 250). The results provide a snapshot of the literature and revealed that research on sexual minority men overwhelmingly focused on HIV, STIs, and sexua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…In line with reviews of the international literature on health among older LGB people ( Addis, Davies, Greene, MacBride-Stewart, & Shepherd, 2009 ; Brennan, Bauer, Bradley, & Tran, 2017 ; McParland & Camic, 2016 ; Potter, Bamford, & Kneale, 2011 ), UK literature on older LGB people’s health is characterized by a focus on specific issues including HIV/AIDS, sexual health, mental health needs, and substance misuse. Much of this evidence is based on studies that do not make direct comparisons with heterosexual people.…”
Section: Evidence On Health and Sexuality In Older Agementioning
confidence: 99%
“…In line with reviews of the international literature on health among older LGB people ( Addis, Davies, Greene, MacBride-Stewart, & Shepherd, 2009 ; Brennan, Bauer, Bradley, & Tran, 2017 ; McParland & Camic, 2016 ; Potter, Bamford, & Kneale, 2011 ), UK literature on older LGB people’s health is characterized by a focus on specific issues including HIV/AIDS, sexual health, mental health needs, and substance misuse. Much of this evidence is based on studies that do not make direct comparisons with heterosexual people.…”
Section: Evidence On Health and Sexuality In Older Agementioning
confidence: 99%
“…In this study, sexual orientation was determined by self-identification [12]. The self-identity sexual orientation of this study was measured by the question: "What is your sexual orientation?"…”
Section: Sexual Orientationmentioning
confidence: 99%
“…Moreover, studies have also shown that HIV-positive MSM have worse mental health than other HIV-positive populations [9,10], while some research found no difference [11]. MSM are defined as sexual minority men from the behavioral dimension of sexual orientation, of which most self-identity as gay or bisexual men (GBM) [12]. Sexual minority men, broadly defined, (a) are men who identify themselves as gay or bisexual, (b) have sexual partners who are male, or (c) are strongly attracted to men [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Millet et al (2005) found that Black MSM were more likely than other racial groups to identify as bisexual. Brennan, Bauer, Bradley, and Tran (2017) suggested that sexual orientation tends to be defined as behavioral in disease-focused research (e.g., MSM), but defined as an identity (e.g., gay) for other research topics.…”
Section: Social Marketing/mass Media Campaignsmentioning
confidence: 99%